2020
DOI: 10.5194/tc-14-2253-2020
|View full text |Cite
|
Sign up to set email alerts
|

Present-day and future Greenland Ice Sheet precipitation frequency from CloudSat observations and the Community Earth System Model

Abstract: Abstract. The dominant mass input component of the Greenland Ice Sheet (GrIS) is precipitation, whose amounts and phase are poorly constrained by observations. Here we use spaceborne radar observations from CloudSat to map the precipitation frequency and phase on the GrIS, and we use those observations, in combination with a satellite simulator to enable direct comparison between observations and model, to evaluate present-day precipitation frequency in the Community Earth System Model (CESM). The observations… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 63 publications
3
18
1
Order By: Relevance
“…Despite the potential for SBIs to act as a barrier for turbulent mixing and hence reduce the rate that aerosol particles are transported down to the surface (Dibb et al, 1992;Li et al, 2019;Thomas et al, 2019), we found no consistent change in N 20 during the first 3 h of SBI events and no relationship between the change in N 20 and the mean intensity of the SBI, which ranges between 0.23 and 0.92 • C m −1 (not shown). SBIs may have a more important role on surface aerosol particle concentrations over longer timescales, especially because the loss of aerosol particles to the surface by dry deposition is slow (Garrett et al, 2010); however, because fog regularly forms during SBI events, it is difficult to isolate the influence of the SBI from the influence of fog scavenging on aerosol particle concentrations during longer events.…”
Section: Controls On Surface Aerosol Particle Concentrations At Summitcontrasting
confidence: 59%
“…Despite the potential for SBIs to act as a barrier for turbulent mixing and hence reduce the rate that aerosol particles are transported down to the surface (Dibb et al, 1992;Li et al, 2019;Thomas et al, 2019), we found no consistent change in N 20 during the first 3 h of SBI events and no relationship between the change in N 20 and the mean intensity of the SBI, which ranges between 0.23 and 0.92 • C m −1 (not shown). SBIs may have a more important role on surface aerosol particle concentrations over longer timescales, especially because the loss of aerosol particles to the surface by dry deposition is slow (Garrett et al, 2010); however, because fog regularly forms during SBI events, it is difficult to isolate the influence of the SBI from the influence of fog scavenging on aerosol particle concentrations during longer events.…”
Section: Controls On Surface Aerosol Particle Concentrations At Summitcontrasting
confidence: 59%
“…Automated weather stations can indirectly measure snowfall using changes in surface height, providing high-temporalresolution data that can resolve accumulation from individual storms (Steffen and Box, 2001); however, the observations are limited to the particular location of the stations and their time period of operation. Both airborne and groundbased radars have been used to detect internal reflecting horizons below the surface to provide historical accumulations over the GrIS (Miège et al, 2013;Lewis et al, 2017), but those values are limited to specific transects, suffer complications from melt events, and only apply on annual or longer timescales. Estimating snowfall frequency and accumulation over the whole ice sheet is often achieved using regional climate models (e.g., Berdahl et al, 2018;Mouginot et al, 2019) or reanalyses (e.g., Schuenemann et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Observed TIRS spectra and the AGHE estimates derived from them allow the contributions to OLR and DLR variability from changes in surface temperature, surface conditions, water vapor, and clouds to be isolated (Wielicki et al, 2013;Huang et al, 2014a (i.e., at a consistent spatial scale) comparisons against monthly gridded, monthly spectral fluxes, AGHE, and cloud impacts on AGHE derived from PREFIRE all-sky and clear-sky spectra. Recent work has highlighted the value of instrument simulators in polar regions for both precipitation (Lenaerts et al, 2020) and clouds/atmospheric opacity (Morrison et al, 2020).…”
Section: Benefit To Polar Modeling and Predictionmentioning
confidence: 99%